2013
DOI: 10.1111/mmi.12293
|View full text |Cite
|
Sign up to set email alerts
|

Human single‐chain urokinase is activated by the omptins PgtE of Salmonella enterica and Pla of Yersinia pestis despite mutations of active site residues

Abstract: SummaryFibrinolysis is important in cell migration and tightly regulated by specific inhibitors and activators; of the latter, urokinase (uPA) associates with enhancement of cell migration. Active uPA is formed through cleavage of the single-chain uPA (scuPA). The Salmonella enterica strain 14028R cleaved human scuPA at the peptide bond Lys158-Ile159, the site cleaved also by the physiological activator human plasmin. The cleavage led to activation of scuPA, while no cleavage or activation were detected with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 52 publications
(148 reference statements)
1
17
0
Order By: Relevance
“…Second, the activity of CroP is not inhibited by common protease inhibitors, including pepstatin A that is a potent inhibitor of aspartic proteases (53). Altogether, these lines of evidence support the reclassification of omptins apart from aspartic proteases, as proposed by others (12,18).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Second, the activity of CroP is not inhibited by common protease inhibitors, including pepstatin A that is a potent inhibitor of aspartic proteases (53). Altogether, these lines of evidence support the reclassification of omptins apart from aspartic proteases, as proposed by others (12,18).…”
Section: Discussionsupporting
confidence: 60%
“…The high-resolution crystal structure of Y. pestis Pla revealed the presence of a water molecule that is activated by the Asp 210 -His 212 dyad and acts as a nucleophile to attack the substrate, while the Asp 83 -Asp 85 dyad is proposed to participate in the stabilization of the catalytic intermediate (10,12,17). Together, these studies showed that omptins combine features of both serine and aspartate proteases and therefore constitute a unique family of proteases (12,18). Previous studies on omptin inhibition reported that Zn 2ϩ , Cu 2ϩ , and benzamidine are able to inhibit OmpT activity (19)(20)(21).…”
mentioning
confidence: 85%
“…This preferential cleavage of the R 7 -K 8 motif was not observed for EHEC OmpT, likely because cleavage of LL-37 by the EHEC ⌬ompT(pEHompT) strain was much faster and fully cleaved LL-37 fragments were obtained within 5 min (4). Though CRAMP also contains two dibasic motifs (R 4 -K 5 and K 15 -K 16 ), we found that most of the cleavage occurred at the K 15 -K 16 motif (Fig. 4).…”
Section: Discussionmentioning
confidence: 89%
“…Omptins are ␤-barrel proteases embedded in the OM and activated by lateral interaction with lipopolysaccharide (LPS) (12)(13)(14)(15). Omptins possess a variety of attributes reminiscent of both serine and aspartic proteases that distinguish them into their own protease class (14,16,17). The omptin catalytic residues consist of two dyads nested within the extracellular active site groove.…”
mentioning
confidence: 99%
“…This consideration stems from their proposed cleavage mechanism, resistance to classical protease inhibitors, neutral pH-optimum, and dependency on bound lipopolysaccharide (LPS). Very recently, we have recorded data that seems to question the well-accepted definition of omptin active site: the Pla mutants D86A, D206A, H208V are inactive in plasminogen activation, as seen before (Kukkonen et al, 2001), but are able to cleave and activate precursor of the human plasminogen activator uPA (Järvinen et al, 2013). Clearly, details of the reaction mechanism of omptins still remain unknown and need further clarification.…”
Section: Structure-function Relationships Of Plamentioning
confidence: 94%